2015
DOI: 10.1111/mmi.13208
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical conversion of C3‐vinyl group to 1‐hydroxyethyl group in bacteriochlorophyll c by the hydratases BchF and BchV: adaptation of green sulfur bacteria to limited‐light environments

Abstract: SummaryPhotosynthetic green sulfur bacteria inhabit anaerobic environments with very low-light conditions. To adapt to such environments, these bacteria have evolved efficient light-harvesting antenna complexes called as chlorosomes, which comprise self-aggregated bacteriochlorophyll c in the model green sulfur, bacterium Chlorobaculum tepidum. The pigment possess a hydroxy group at the C3 1 position that produces a chiral center with R-or S-stereochemistry and the C3 1 -hydroxy group serves as a connecting mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…The BchF and BchV enzymes from Cba. tepidum were prepared as described previously , and soluble fraction of the lysate of E. coli transformed to produce BchF or BchV enzymes was used in this experiment. BchF or BchV in 50 m m Tris‐HCl buffer (pH 7.8) was incubated with BchC on ice for 10 min, then used for the coupled assays.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The BchF and BchV enzymes from Cba. tepidum were prepared as described previously , and soluble fraction of the lysate of E. coli transformed to produce BchF or BchV enzymes was used in this experiment. BchF or BchV in 50 m m Tris‐HCl buffer (pH 7.8) was incubated with BchC on ice for 10 min, then used for the coupled assays.…”
Section: Methodsmentioning
confidence: 99%
“…One is dehydrogenation of the C7=C8 double bond by Chlide a oxidoreductase (COR), resulting in the formation of a bacteriochlorin ring . The other two steps are hydration of the 3‐vinyl (3V) group by BchF (hydratase) and oxidation of the resultant 3‐(1‐hydroxyethyl) (3HE) group by BchC (oxidoreductase) to introduce the 3‐acetyl (3Ac) group (3‐CH=CH 2 → 3‐C*H(OH)CH 3 → 3‐COCH 3 ) . Since the 3HE group introduced by BchF becomes a substrate for oxidation by BchC, the order cannot be inverted; BchF‐catalyzed hydration must be followed by BchC‐catalyzed oxidation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that one gene in this cluster, cruB, encodes a ␥-carotene cyclase that is essential for the synthesis of ␤-carotene and isorenieratene, carotenoids that are uniquely and nearly universally produced by brown-colored GSB (42). This gene cluster also includes a third homolog of bchF and bchV, genes that encode C-3 vinyl hydratases (21,(27)(28)(29).…”
mentioning
confidence: 99%
“…BchQ and BchR methylate the resulting product at the C-8 2 and C-12 1 positions, respectively, to produce a family of related homologs (18). These methylation homologs are then hydroxylated at C-3 1 by BchF or BchV to produce bacteriochlorophyllide (BChlide) d (21,(27)(28)(29), and in BChl c-producing strains, they are subsequently methylated by BchU at C-20 to produce BChlide c homologs (12,30,31). Finally, the BChlide c or BChlide d homologs are esterified with farnesol pyrophosphate by BchK to produce BChl c or BChl d homologs with differing numbers of methyl groups (20).…”
mentioning
confidence: 99%